EFFECTIVITY OF NIPAH (Nypa fruticans) EXTRACT ON (Aedes aegypti) LARVAE IN BRACKISH WATER - Rady, Rady; Effendi, Irwan; Feliatra, Feli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
The most commonly used method of vektor control is temephos (the synthetic larvicide). Currently in some areas there has been resistance of aedes aegypti larvae to temephos, so that natural larvicide is required as an alternative. Nypa exctract contains flavonoid compounds that are respiratory toxins that can kill aedes aegypty larvae.This research was conducted in January - February 2019. The purpose of this study was to determine the inhibitory power of nipah extract against larvae in brackhish water. The results of this study are expected to increase knowledge and provide information about the pontential of nipah as a soursce of bioactive compounds. The method used is the experimental method, where the location of the research sampel was obtained at one sampling location point in the Sungai Kayu Ara village, Siak Riau province. The results showed that the average mortality of larvae in nipah laeves in the 60th minute was 55, 80, 100 and 100%. While root extracts have larvae deaths as many as 60 minutes, namely 100, 90, 90, and 100%. For the average mortality of larvae at the root of nipah there are 60 minutes, which are 95, 100, 100 and 100%. As wel as positive and negative controls as a comparison. So it can be compared to 3 administration of nipah extract both leaves, roots and midrib so that the three conncentrations used are better than the use of midrib extract compared to leaf and root extract. It can be concluded that the more concentration used the higher the mortality of larvae is the concentration of 12%. For the concentration used the percentage of larvae mortality in the test media is as much as 6%, 9% and 12%. Every death of larvae has reristance to different bodies so that at the 30th minute there is a difference in mortality of larvae wich a given concentration. The larvae species used are aedes aegyti larvae. The highest mortality of dead es was found in midrib extract and also positive controls. So that the death of larvae is very effective against the given solution has the same ability. The mortality of A. aegypti larvae were then analyzed using probit analysis to obtain LC50 (Lethal Concentration 50) and LT50 (Lethal Time 50) values. The results of the probit analysis of leaf, root and midrib extracts are the estimation of LC50 1.493, 2.618, 0.005. while leaf , root and midrib extracts at the LT50 estimate were 2.841, 1.579, 2.227